2016
DOI: 10.1007/s12053-016-9459-2
|View full text |Cite
|
Sign up to set email alerts
|

Wind energy integration via residential appliances

Abstract: In this paper cold and thermal storage options via wind energy surplus are examined aiming to enable higher wind integration. A case study in Greece with an installed wind farm (WF) was investigated reviewing the possibilities for higher renewables integration using thermostatically controlled loads (TCLs), analysing thermal and cold storage possibilities according to the needs of the local municipalities. The basic aim is to describe the idea of an aggregated system with a number of residential freezers, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The global energy consumption is estimated to increase between 2010 and 2040 by 56% (U.S. Department of Energy, 2016). Despite the decreasing coal, petroleum and natural gas resources, and all the issues their appliance evoke (such as global warming and climate change), in 2015, the share of fossil fuels was 78.4% of the final global energy consumption, while renewables and nuclear power considering the advantage that the energy is then being produced close to the location where it is needed (Xydis, 2015;Xydis and Mihet-Popa, 2016;Stathopoulos et al, 2018).…”
Section: Background Of the Researchmentioning
confidence: 99%
“…The global energy consumption is estimated to increase between 2010 and 2040 by 56% (U.S. Department of Energy, 2016). Despite the decreasing coal, petroleum and natural gas resources, and all the issues their appliance evoke (such as global warming and climate change), in 2015, the share of fossil fuels was 78.4% of the final global energy consumption, while renewables and nuclear power considering the advantage that the energy is then being produced close to the location where it is needed (Xydis, 2015;Xydis and Mihet-Popa, 2016;Stathopoulos et al, 2018).…”
Section: Background Of the Researchmentioning
confidence: 99%
“…Similar studies were also found in the literature focused on autonomous buildings and isolated grids. 8,9 Based on the assumption that end-users are unwilling or unable to alter their electricity consumer behaviour, operation and management supply side draws more attention than the demand, in most traditional power systems. As a result, there are higher generation expenses for the operator coming from the operation of expensive conventional plants committed to contribute only at peak times (demand is usually met by lower cost base load units, during off-peak periods).…”
Section: Energy Demand and Electricity Marketsmentioning
confidence: 99%
“…Whilst there is a large body of work describing the use of TES systems for demand-side management (see review by Sun et al 2013), only two recent studies detail the impact of integrated control of PV and ice thermal energy storage using energy modelling tools (Wang and Dennis 2015;Sehar et al 2016) and one described the use of surplus wind energy and thermal storage (Xydis and Mihet-Popa 2016). This study is unique as it examines an end-user-operated direct digital control (DDC) BMS that controls HVAC with integrated chilled water TES, and the chilling of a large 3.2-ML aquarium tank, in order to optimise solar PV energy generation use in the absence of electrical battery storage.…”
Section: Related Workmentioning
confidence: 99%